MENGEMBANGKAN KEMAMPUAN MENGURUTKAN URUTAN BILANGAN PADA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN TRADISIONAL PELANGKUNG MODIFIKASI DESA LANGAN KABUPATEN MELAWI KALIMANTAN BARAT - Tresia Afila; Lukmanulhakim Lukmanulhakim; Annisa Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Playing is one of the needs of early childhood and is an important tool in their learning process, including developing cognitive abilities. One aspect of cognitive development is the ability to sequence numbers. This study aims to determine the ability of children aged 5-6 years in sequencing numbers through the traditional game of Pelangkung in Langan Village, West Kalimantan. The research method used a descriptive qualitative approach with participatory observation techniques, involving two 6-year-old children as research subjects. The results show that the Pelangkung game has the potential to help children understand number sequences through the activity of counting and taking game stones sequentially, thereby developing their ability to determine number sequences more accurately and independently.